2018
DOI: 10.1177/1744987118809482
|View full text |Cite
|
Sign up to set email alerts
|

Hidden voices: an interpretative phenomenological analysis of the experience of surviving breast cancer in Saudi Arabia

Abstract: Background Women with breast cancer often have difficulties in making sense of and understanding their experiences, specifically the ways in which cultural sensitivities impact on and shape their lifeworlds. Aims The aim of this study is to explore the experience of being a breast cancer survivor in Saudi Arabia. Methods Qualitative, in-depth, semi-structured interviews were conducted with 18 Saudi breast cancer survivors aged between 30 and 50 years who had finished treatment 6–47 months before data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Similarly, a qualitative study on eighteen women with BC in Saudi Arabia showed that belief in God and following God's commands were reflected in the feeling of a duty to please their husbands. Therefore, they decided to continue their marital relationships and lifestyle based on previous life routines [38]. A systematic review by Chang et al, concluded that religious beliefs were inseparable from sexuality and affected the reactions of patients with BC to sexual issues [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a qualitative study on eighteen women with BC in Saudi Arabia showed that belief in God and following God's commands were reflected in the feeling of a duty to please their husbands. Therefore, they decided to continue their marital relationships and lifestyle based on previous life routines [38]. A systematic review by Chang et al, concluded that religious beliefs were inseparable from sexuality and affected the reactions of patients with BC to sexual issues [15].…”
Section: Discussionmentioning
confidence: 99%
“…The responses of husbands and families were sometimes challenging for the respondents. Although husbands tended to be valued as sources of emotional and financial support, there were occasions where married Arab women were afraid that their husbands may divorce them or take a second wife, because they were no longer fertile or sexually attractive [25,30,32,36]. There were infrequent examples in the literature where these fears were realised, with the rupture of sexual relationships, separation, divorce, and physical or emotional spousal abuse being experienced [24,26,30,32,35,36].…”
Section: Theme 2 Coping With Breast Cancermentioning
confidence: 99%
“…Arab women found it difficult to cope with society's negative reactions to their illness. These were characterised as being pitied, shunned and blamed for having breast cancer [25,26,29,31,33,36,38]. Respondents felt that many people, including friends and work colleagues, feared them and avoided them because of a fear that breast cancer was contagious.…”
Section: Theme 2 Coping With Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations